Factors effecting the development of sentinel lymph node metastasis in clinical early-stage breast cancers (cT1-2N0): Clinical significance of primary tumor – skin distance - Zirek, Levent; Lale, Azmi; Zirek, Merve; Lale, Hatice Nur; Yildirir, Ali Cihan; Aygen, Erhan (My University, 2021)
Aim: It was aimed to determine the demographic, clinicopathological and radiological predictors that may be effective in the development of sentinel lymph node (SLN) metastasis in patients with clinical early-stage breast cancer (cT1-2N0). Materials and Methods: 178 patients were included in the study. Demographic, clinicopathological and radiological characteristics of the patients were recorded. Among these, there were age, neutrophil / lymphocyte ratio (NLR), HER2, estrogen receptor (ER) and progesterone receptor (PR), proliferation index (Ki- 67), morphological grade, molecular subtype, histopathological subtype, tumor size and localization, multifocality and multicentricity, nipple-areola complex (NAC) infiltration, perineural invasion (PNI), lymphatic invasion (LI), vascular invasion (VI), primary tumor -breast skin distance (DFS). Results: Larger tumor size, HER-2 positivity, grade 3 histopathology, LI, VI, PNI, and closer DFS were found to be significant in univariate regression analyzes. In ROC analysis, the optimum cut-off value for DFS was found to be 13.5mm. In multivariant regression analyzes, HER-2 positivity, LI, PNI and ?13.5mm DFS were found as independent SLN metastasis predictors. Conclusion: Closer DFS, HER-2 positivity, LI and PNI are very strong predictors in patients with clinical early-stage breast cancer that must be taken into account in the development of SLN metastasis in cT1-2N0 breast cancers. These factors can guide clinicians to take accurate decisions in the treatment process.
Keywords: Onkoloji